Too much is not always good: the inverted U-shaped link between green customer integration and opportunistic behavior. Issue 5 (3rd September 2021) - Shi, Haiqing; Feng, Taiwen; Li, Zhiyi
Abstract : Purpose: The purpose of this study is to explore the inverted U-shaped relationship between green customer integration (GCI) and opportunistic behavior, as well as the moderating effects of contractual control and relational norms. Design/methodology/approach: The authors conducted hierarchical regression analysis using two-waved data from 206 Chinese manufacturing firms to test hypotheses. Findings: The authors found that GCI has an inverted U-shaped effect on opportunistic behavior. Furthermore, both contractual control and relational norms negatively moderate the inverted U-shaped relationship between GCI and opportunistic behavior. Originality/value: This study uncovers an inverted U-shaped link between GCI and opportunistic behavior by combining transaction cost economics and social exchange theory. Furthermore, this study reveals contractual control and relational norms can be deemed as two boundary conditions affecting the inverted U-shaped GCI–opportunistic behavior relationship. This study also offers managerial implications for firms curbing opportunistic behavior that may result from GCI.